Pengukuran Efektivitas Kerangka PDREF melalui Aktivitas Menulis Kolaboratif dalam Pembelajaran Penulisan Esai Deskriptif - Hesty Puspita Sari; Priden’na Nurri’yan (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The ability to write descriptive essays is an essential competence for students of English as a Foreign Language (EFL). However, many students still face difficulties in organizing ideas and producing systematic writing. This study aims to measure the effectiveness of the PDREF framework (Planning, Drafting, Revising, Editing, and Final Draft) in teaching descriptive essay writing. PDREF was applied as a process-oriented instructional framework in teaching writing. This study employed a quantitative approach using a one-group pre-test and post-test design. The participants of this study were 10 students from the English Education Department at Universitas Islam Balitar. The data were analyzed using a paired sample t-test through SPSS. The results of the analysis showed a significant improvement in students’ writing ability, with the mean score increasing from 65.40 in the pre-test to 82.70 in the post-test. The paired sample t-test result indicated a significance value of 0.000 (Sig. 2-tailed < 0.05), which means that there was a significant difference before and after the implementation of the PDREF framework. Therefore, the PDREF framework is found to be effective in improving EFL students’ descriptive essay writing skills, particularly in terms of idea organization and descriptive quality.